Bidirectional Ventricular Tachycardia due to Pheochromocytoma: A Case Report - Gui‐yang Li; Man‐Xin Lin; Fa‐Guang Zhou; Qiang Li (Annals of Noninvasive Electrocardiology)
ABSTRACT Pheochromocytoma, a type of neuroendocrine tumor, can cause numerous symptoms and signs similar to those of other clinical conditions, with the classic triad being palpitations, headache, and diaphoresis. Patients with pheochromocytoma can present with various cardiac complications, including myocarditis, acute coronary syndromes, cardiomyopathy, heart failure, and arrhythmias. Here we report a case of pheochromocytoma that first presented with bidirectional ventricular tachycardia. The patient was initially diagnosed with acute viral myocarditis and was treated accordingly. A pheochromocytoma crisis with severe blood pressure fluctuation occurred after glucocorticoid administration, leading to further diagnostic work‐up, which eventually revealed the adrenal pheochromocytoma.